The The Use of Scramble Technique in Teaching Literacy For Fourth Grade Student At Sanggar Bimbingan Hulu Kelang Malaysia - Fadhilah; zulfa (E-Link Journal, 2024)
This can be seen from the lack of knowledge in making simple sentences owned by students and difficulties in composing sentences properly. In addition, students' lack of attention to the teacher's explanation, lack of writing practice and feel less confident and worried that they will be laughed at by the surrounding environment if they make mistakes. So this research want to know the implementation of scramble technique in teaching literacy and students and teacher perception on the use of scramble teachnique in teaching literacy. This study uses case study. . The object of research is fourth grade students at Sanggar Bimbingan Hulu Kelang Malaysia as many as 6 students. From this study suggest that scramble technique is an effective pedagogical tool to improve writing skills of fourth grade. By combining structured guidance with engaging and interactive activities, this method successfully improves the ability to write simple sentences and self-confidence of fourth grade students of Sanggar Bimbingan Hulu Kelang Malaysia.